167k views
23 votes
Evaluate x4 + 4x3 - 2x2 + 11x - 6 for x = 3

2 Answers

5 votes

Explanation:


f(x) = {x}^(4) + 4 {x}^(3) - 2 {x}^(2) + 11x - 6


f(3) = {3}^(4) + 4. {3}^(3) - 2. {3}^(2) + 11.3 - 6


f(3) = 81 + 4.27 - 2.9 + 33 - 6


f(3) = 81 + 108 - 18 + 33 - 6


f(3) = 198

User Steve Gury
by
6.3k points
0 votes

Answer:

198

Explanation:

x4 + 4x3 - 2x2 + 11x - 6 for x = 3

3^4 + 4 * 3^3 - 2 * 3^2 + 11 * 3 - 6 =

81 + 4 * 27 - 2 * 9 + 11 * 3 - 6 =

81 + 108 - 18 + 33 - 6 =

198

User Marcel De Castilho
by
6.3k points